2017
DOI: 10.3747/pdi.2016.00039
|View full text |Cite
|
Sign up to set email alerts
|

Peritoneal Dialysis in Very Low Birth Weight Neonates

Abstract: Acute PD is still an appropriate treatment choice for VLBW neonates with AKI. In VLBW neonates, PD can be performed with an improvised PD system and catheters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 32 publications
1
30
0
3
Order By: Relevance
“…Some complications associated with PD in premature infants include mechanical dysfunctions, such as dialysate leakage and catheter obstruction requiring revision or reinsertion, intraperitoneal hemorrhage, and bowel perforation [17,20,29]. Peritoneal fluid leakage around the PD catheter and along the tunnel is a serious problem that can increase the risk of bacterial and fungal peritonitis [21,30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some complications associated with PD in premature infants include mechanical dysfunctions, such as dialysate leakage and catheter obstruction requiring revision or reinsertion, intraperitoneal hemorrhage, and bowel perforation [17,20,29]. Peritoneal fluid leakage around the PD catheter and along the tunnel is a serious problem that can increase the risk of bacterial and fungal peritonitis [21,30].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the complications observed in relation to PD were mainly caused by catheterrelated dialysate leakage, which was resolved after adjustment of the dwell volume or reinsertion of the catheter on the other side. In a previous study, a tissue adhesive, i.e., commercially available fibrin glue, was used at the insertion site [29]. Therefore, selection of an optimal catheter for PD is very important to minimize the complications associated with PD access.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the complications observed in relation to PD were mainly caused by catheter-related dialysate leakage, which was resolved after adjustment of the dwell volume or reinsertion of the catheter on the other side. In a previous study, a tissue adhesive, i.e., commercially available brin glue, was used at the insertion site [32]. Therefore, selection of an optimal catheter for PD is very important to minimize the complications associated with PD access.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that acute PD is still an appropriate treatment option for VLBW newborns with AKI [15,32,40]. Furthermore, some studies have reported PD experiences in extremely immature infants [14, 17, 20-23, 31, 40, 41].…”
Section: Discussionmentioning
confidence: 99%
“…La mortalidad de los RN con LRA que realizan DP es muy elevada (del 50 % al 80 %), 24,25 sobre todo, porque se instaura en neonatos gravemente comprometidos.…”
Section: Complicaciones De La Diálisis Peritonealunclassified